2021
DOI: 10.3389/fevo.2020.623627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grazing Enclosures on Species Diversity, Phenology, Biomass, and Carrying Capacity in Borana Rangeland, Southern Ethiopia

Abstract: A grazing enclosure (GE) is one of the most effective techniques for restoring degraded rangelands by modifying the composition, abundance, and diversity of species. However, the effect of GEs on different grazing intensities and durations compared to open-grazing (OG) rangelands is not well known. We aimed to assess the effect of GE on the characteristics of plant species. We established five plots in a short-term enclosure, a long-term enclosure, and an OG treatment to examine the effect of GE on vegetation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 58 publications
4
15
0
Order By: Relevance
“…In each grazing land type, three grazing treatments were categorized based on GI. Grazing intensity data were collected using the same procedures described by Fenetahun et al (2020Fenetahun et al ( ,2021, the same authors at the same study site. Based on the discussion and survey data, grazing sites were chosen based on similar, uniform, and same soil series.…”
Section: Grazing Site Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In each grazing land type, three grazing treatments were categorized based on GI. Grazing intensity data were collected using the same procedures described by Fenetahun et al (2020Fenetahun et al ( ,2021, the same authors at the same study site. Based on the discussion and survey data, grazing sites were chosen based on similar, uniform, and same soil series.…”
Section: Grazing Site Selectionmentioning
confidence: 99%
“…We selected a site with two treatments: a non-grazing (NG) (as a control) and a grazing site (moderately grazing and overgrazing) that was considered to see the effect of grazing intensity based on grazing intensity gradient (Fenetahun et al, 2021). The rate of GI was described as follows: non-grazed (NG) (livestock have been excluded from the pasture by fence and the ground was almost completely covered by vegetation) and moderately grazed (MG) (pasture has been used for grazing in regular Dividing oven-dry mass to volume of the core sampler Alemayehu and Fisseha (2018); Wilke (2005) rotational basis, that is, used during non-dry seasons but not in the rainy season and vegetation covers almost 50-55% and overgrazed (OG) (pasture is used for grazing constantly throughout the year and totally grazed and undergoes degradation, and vegetation cover was in most cases less than 15%) for the last 1.5 years, and also, GI was divided into MG and OG based on the current carrying capacity potential (Fenetahun et al, 2020;Fenetahun et al, 2021). The treatments of sample collection involved at NG (∼0 ha AU −1 Y −1 ), MG (6 ha AU −1 Y −1 ), and OG (12 ha AU −1 Y −1 and above) grazing area based on the current carrying capacity of rangeland was calculated by Fenetahun et al (2020) and physical field observation.…”
Section: Grazing Site Selectionmentioning
confidence: 99%
“…They can promote ecosystem succession and restore ecosystem stability [13,14]. Additionally, the enclosures significantly improve soil physicochemical properties, water content, soil organic carbon, nitrogen, and phosphorus [15][16][17]; above-and below-ground biomass; productivity; species richness, evenness and complexity; soil microbial diversity, and ecosystem structure and function [18][19][20][21][22]. However, their effectiveness is influenced by the ecosystem types, the degree of degradation, the fencing enclosure method, and the time length [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the richness of grasses can affect the richness of herbivores by providing a more diverse food supply, following the logic of the predator-prey relationship (e.g., Kallay andCohen 2008, Malard et al 2020). It is impossible to solve this dilemma using comparative data, and even exclosure experiments tend to give ambiguous results (Chikorowondo et al 2017, Li et al 2017, Fenetahun et al 2021. Moreover, it is likely that both mechanisms with opposite directions are in play with differing importance depending on the specific environmental settings.…”
Section: Causality Of the Relationship Between Grasses And Herbivores...mentioning
confidence: 99%
“…It has been reported that plant species diversity in savannas, including that of grasses, is often positively affected by free-ranging large herbivores (Olff and Ritchie 1998, Anderson et al 2007, Díaz et al 2007, Jacobs and Naiman 2008, Staver and Bond 2014. Grass diversity is expected to be highest under intermediate herbivore pressure because under high pressure, only species adapted to disturbance survive, as demonstrated by papers studying the effect of artificial water points or conducted in smaller game reserves (Thrash et al 1993, Todd 2006, Smit and Grant 2009, Fenetahun et al 2021), while at low densities or when herbivores are excluded, a few dominant grass species tend to prevail (Olff and Ritchie 1998, Anderson et al 2007. By this mechanism, grazing affects competitive relationships among grass species.…”
Section: Introductionmentioning
confidence: 99%